Determinants of stillbirths occurred in health facilities in Zambezia province, Mozambique (2013-2014) - Germano Pires; Maria Rosa; Minó Zangarote; Sérgio Chicumbe
Abstract Objectives: to identify the determinants of stillbirths in Zambezia province, Mozambique. Methods: a retrospective cross-sectional ecological study was carried out in 2013-2014 by using perinatal indicators captured by the health information system in Zambezia. Sequentially perinatal care indicators, bivariate analysis and multiple adjusted regression at a 5% significance level with possible explainable variables of stillbirths were described. Results: a median proportion of stillbirths was 1.6%, low birth weight and preterm birth and obstetric complications were 4.9%, 1.9% and 4.1%, respectively. The bivariate analysis demonstrated association of stillbirths with anemia (p=0.043), antepartum hemorrhage (p=0.009), dystocic delivery (p<0.001), obstructed labor (p=0.004). In the analysis of multiple adjusted regression, the obstructed labor were a predictor (ß=0.435; p=0.03) to stillbirths Conclusions: the most important factor associated to stillbirths in health facilities in Zambezia province in 2013-2014 was the obstructed labor. The strengthening of diagnostic analysis and the attempt to handle obstetric complications is still a priority in Zambezia, in being able to decrease the avoidable perinatal deaths.